Ricochet : - Feldman, Richard (John Wiley & Sons, 2008)
Ricochet Confessions Of A Gun Lobbyist. "Ricochet tells the truth. With each page I can hear the echo of footsteps down the Rayburn Building's marbled halls as Feldman tells the intimate story few know and even fewer survive." —Jack Brooks (D-Tex.), former Chairman, U.S. House Judiciary Committee